The teaching of home economics to the mentally retarded children of Jose Fabella Memorial School - Padilla, Josefina Bajit 1932-; Saquido, Rizalina D. (Quezon City College of Education, University of the Philippines Diliman, 1968)
The aim of the study was to propose a functional Home Economics program for the mentally retarded children in the intermediate level of the Jose Fabella Memorial School. The approaches used in securing the material and the data discussed were as follows: review of related literature and interviews of house parents, social workers, school personnel such as counselor and psychologist, teachers and school administrators of special schools and schools with special classes. The home economics program for the educable mentally retarded children starts with the intermediate or preadolescent group where fundamental experiences are provided in sewing, cooking, clothing, needlework, and homemaking to both girls and boys. Additional area of study in home economics is child care.
"February, 1968."
Vita.
Thesis (Master of Arts in Teaching : Special Education : Mental Retardation)--University of the Philippines, Diliman.
Keywords: Home economics -- Study and teaching (Secondary) -- Philippines; Gifted children -- Education (Secondary) -- Philippines